Analysis of Amyloid-β Peptides in Cerebrospinal Fluid Samples by Capillary Electrophoresis Coupled with LIF Detection - Verpillot, Romain; Esselmann, Hermann; Mohamadi, Mohamad Reza; Klafki, Hans; Poirier, Florence; Lehnert, Stefan; Otto, Markus; Wiltfang, Jens; Jean-Louis, Viovy; Taverna, Myriam (Analytical chemistry (Washington), 2011)
We report a CE-LIF method for the separation and detection of five synthetic amyloid-β peptides corresponding to an important family of CSF-biomarkers in the context of Alzheimer disease (AD). The presumed most relevant peptides (Aβ1-42, Aβ1-40, and Aβ1-38) that may support the differentiation between AD and healthy patients or other dementias were successfully detected in CSF by incorporating an immunoconcentration step prior to CE analysis of derivatized peptides. We labeled the Aβ peptides with a fluoroprobe dye before CE-LIF analysis. This reagent reacts with the amino groups of lysine residues and produced mostly ditagged Aβ peptides under the proposed experimental conditions. The labeling reaction displayed similar efficiency with each one of the five different synthetic Aβ peptides that were tested. The limit of detection of the CE-LIF method approached 280 attomoles of injected synthetic labeled Aβ peptides. We obtained excellent correlation between peak areas and peptide concentrations from 35 nM to 750 nM. For the detection of Aβ peptides in human CSF samples, we enriched the peptides by immunoprecipitation prior to the CE-LIF analysis. The comparison of the CE-LIF profiles obtained from CSF samples from 3 AD patients and 4 non-demented control subjects indicated noticeable differences, suggesting that this method, which relies on a multibiomarker approach, may have potential as a clinical diagnostic test for AD.